Analysis of unconditional conservatism and earnings quality of financial reporting practices in Indonesia upon IFRS covergence / Monica Santi, Erlane K Ghani and Evita Puspitasari. - Santi, Monica; K Ghani, Erlane; Puspitasari, Evita (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2017)
This study examines the unconditional conservatism and earnings quality as part of corporate governance before and after IFRS convergence in Indonesia. Specifically, this study examines the effect of eliminating the conservatism concept within the accounting framework following the development of principle based accounting standard and earnings quality on financial reporting practices. This study further examines the effect of eliminating conservatism concept to the earnings quality upon implementation of IFRS convergence on the financial reporting practices. Using content analysis on 180 annual reports of 36 manufacturinglisted companies over a 5 year period in Indonesia, this study found that unconditional conservatism has not changed significantly after IFRS convergence. However, the earnings quality of the manufacturing companies has declined upon IFRS convergence. This study also found that unconditional conservatism has positive influence on earnings quality upon IFRS convergence although the result is insignificant. From the agency theory perspective, this study highlights the introduction of accounting and governance reform on the principal-agent relationship in relation to the unconditional conservatism and earnings quality practices. The findings in this study shed some lights to the regulators, practitioners and other interested parties on the implication of IFRS convergence in a developing country such as Indonesia.